Assessment of iron bioavailability from twenty elite latematuring tropical maize varieties using an in vitro digestion/Caco2 cell model - Oikeh, S.O.; Menkir, A.; Maziya-Dixon, B.B.; Welch, R.M.; Glahn, Raymond P. (Wiley, 2004)
An in vitro digestion/Caco-2 cell model was used to assess iron bioavailability of twenty elite late-maturing tropical maize varieties grown in three diverse agroecologies in West and Central Africa (WCA). Kernel-iron concentration of the varieties, averaged across locations, varied from 19.2 to 24.4 mg kg−1, while mean kernel-zinc concentration ranged between 19.4 and 24.6 mg kg−1. Significant differences in iron bioavailability were observed among varieties, but the environment had no significant effect. Mean bioavailable iron ranged between 14% below and 43% above the reference control variety, TZB-SR. Variety DMR-LSR-Y with the highest concentrations of kernel-iron and -zinc of 24–25 mg kg−1 across the three locations had a similar quantity of bioavailable iron as the reference control, TZB-SR. In the long run this variety could be potentially effective in reducing iron deficiency because of its high kernel-iron. The most promising varieties were Mid-altitude STR synthetic and ACR91SUWAN-1-SRC1. They had kernel-iron and -zinc levels of 22–24 mg kg−1 and bioavailable iron 24–36% higher than the reference control, TZB-SR. Additional research is necessary to determine if the increases in kernel-iron concentration and bioavailable iron observed in this study can significantly improve the iron status of individuals in WCA at risk for iron deficiency.